Fear of death and structure of personality with men in the early and late adulthood - Zawadzka, Agnieszka; Dębska, Agnieszka; Zawadzki, Łukasz (Journal of Education, Health and Sport, 2017)
Introduction. Fear of death is the fear of ending one’s own existence. While a man grows up he/she is aware that his/her life will be ended with death. Nevertheless, the awareness does not reduce the fear. An individual can see, hear, experience. He/she is surrounded by loved people, is determined in pursuin his/her goals and death ends it all, it is the absolete end. Therefore, everyone is more or less affraid of it. Aim. The aim of the study is to verify if there are any differences in the level of fear of death among chosen age groups. What affects and conditions them. Materials and methods. The study involved 60 men divided on two age groups. The first one were 30 men in their early adulthood aged 23 – 28. The secong one were 30 men in their late adulthood aged 60 and more. The research tools were two questionnaires FTVS – Fear of death and dying inventory by R. Oschmann and NEO-PI-R Five Factor Model (FFM). Results. Men in their early and late adulthood experience fear of death in similar manner, fear of facing death, fear of mortality, fear of ending one’s existence, fear of physical destruction, fear of live after death and fear of dying proces. Personal characteristics relate with fear of death differently in gropus of men in early and late adulthood. Keywords: fear, personality, death,